2021
DOI: 10.1108/ils-05-2020-0162
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing instructional outcomes with a serious gamified system: a qualitative investigation of student perceptions

Abstract: Purpose This paper aims to evaluate the students’ perception of their learning experiences concerning serious gaming and gamification instructions and determines whether they were motivated enough and engaged during the educative process in a resource-poor context. Moreover, the study evaluated the impact of interactive instructional environment outcomes in terms of students’ perceptions of the learning catalysed by gamified systems, particularly in enhancing attitude change coupled with knowledge acquisition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…However, our findings are different in that they suggest that it is important to incorporate the right game elements to have a positive impact on the training outcomes. These results contribute to recent theoretical debates about the role of gamified training in corporates training (Saleem et al, 2022;Haruna et al, 2021). Our findings imply that bonding forms of game elements, represented by learning outcomes, are valuable for making the training programs effective in the organization.…”
Section: Discussionsupporting
confidence: 72%
“…However, our findings are different in that they suggest that it is important to incorporate the right game elements to have a positive impact on the training outcomes. These results contribute to recent theoretical debates about the role of gamified training in corporates training (Saleem et al, 2022;Haruna et al, 2021). Our findings imply that bonding forms of game elements, represented by learning outcomes, are valuable for making the training programs effective in the organization.…”
Section: Discussionsupporting
confidence: 72%
“…Instructional techniques should provide a sense of satisfaction and interactivity from students because they have been found to enhance learning outcomes and motivation. Research studies have shown that learner-centered instruction, multimodal presentation systems, serious gaming and gamification instructions, collaborative learning techniques, and blended teaching strategies and materials are effective in increasing learning effectiveness, satisfaction, and motivation (Yang et al, 2022;Haruna et al, 2021;Kuo et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the use of EDG in teaching processes improves students' concept perception, increases their active participation, and motivates them to learn in a more interactive environment (Ferrer, Martinez, and Ibáñez, 2020). EDG have the potential to be an effective tool in mathematics teaching due to their interactive nature (Buchori and Sudargo, 2016;Haruna, Abbas, Zainuddin, Hu, Mellecker, and Hosseini, 2021;Hwang, Chien, and Li, 2021;Hayati and Behnamnia, 2023;Yusof and Shahrill, 2021;Aktaş, Bulut and Aktaş, 2022;Videnovik, Vold, Dimova, Kiønig, and Trajkovik, 2022).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%